The Photocatalytic Activity of Green Zinc Oxide Nanoparticles in The Treatment of Aerobically Palm Oil Mill Effluent - Abu Bakar Sidik, Dilaeleyana; Hairom, Nur Hanis Hayati; Rozman, Aniq Ikhmal; Johari, Mohamad Jauhar Shaqili; Muhammad, Aida (Journal of Science and Technology, 2023)
Traditional treatment of aerobically palm oil mill effluent (A-POME) is incapable of removing the colour and organic load that does not exceed the discharge standard limit to the stream channel. Green synthesis nanoparticles (NPs) provide a significant potential for substantial performance in the photocatalytic degradation of high-strength wastewater. Therefore, the current project's goal is to investigate the photocatalytic degradation performance of A-POME in the addition of green Zinc Oxide Cymbopogon Citratus (ZnO–CC) NPs in terms of chemical oxygen demand (COD), turbidity, and colour removal. The outcomes showed that pH 8 and a ZnO-CC NPs loading of 0.3g/L was ideal for the photocatalytic degradation of A-POME with a significant percentage reduction of turbidity (68.03%), colour (48.11%), and COD (75.4%). The equilibrium data revealed a better fit Langmuir-Hinshelwood models with higher R2 and K values of 0.9906 and 0.0225, respectively. Increased ZnO–CC NPs loading in alkaline medium aided in the breakdown of A-POME pollutants by increasing the surface area accessible for UV light adsorption during the photocatalytic process. Thus, the finding from this study can assist the palm oil mill sector in improving A-POME treatment to provide high-quality treated effluent.